2022
DOI: 10.1017/cts.2022.441
|View full text |Cite
|
Sign up to set email alerts
|

Providing peer navigation services to women with a history of opioid misuse pre- and post-release from jail: A program description

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In initial interviews, peers described transitions as unpredictable and discussed barriers related to stigma and establishing relationships via telehealth. However, they also discussed that peer navigation can offer critical linkages to services for women during release from jail ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In initial interviews, peers described transitions as unpredictable and discussed barriers related to stigma and establishing relationships via telehealth. However, they also discussed that peer navigation can offer critical linkages to services for women during release from jail ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Third, programs demonstrated that education on MOUD helps improve long-term health and reincarceration outcomes when coupled with other treatment assistance ( 26 ). Finally, while the records showed mixed results, care and/or peer navigation show potential in facilitating treatment engagement within the community ( 26 , 34 , 37 ). Future efforts should scale up these interventions and programs and explore generalizability and long-term effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A particularly promising area of OUD recovery research is how peer-led interventions can help affected women navigate MOUD treatment and reintegration into work and home life (Tillson et al, 2022). In the present study, peer recovery coaches were identified as providing invaluable assistance to women in recovery, with extant literature also highlighting the benefits of integrating peer recovery supports into traditional MOUD treatment programs (Bergman et al, 2019; Kelly et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence supports the effectiveness of the Transitions Clinics Network model, which addresses the social determinants of health while providing OUD treatment (Howell et al, 2021). Peer navigation is another emerging method for providing support to individuals with OUD who are re-integrating into the community (Belenko et al, 2021;Bellamy et al, 2019;Tillson et al, 2022). Digital technology could also offer a novel method for providing or extending re-entry supports.…”
Section: Discussionmentioning
confidence: 99%